Preeclampsia in twin pregnancy - Francisco,Carla (2019)
Twin pregnancy is a high-risk condition and its incidence has raised over the last decades. Hypertensive disorders are among the most common medical complications of pregnancy. While is unquestionable that multiple pregnancy has an increased risk of preeclampsia (PE), it's unclear what are the other risk factors. The pathophysiology of PE is uncertain but is thought to be a condition of poor placentation, resulting in generalized vascular endothelial activation and vasospasm. Published data also show that an angiogenic/anti-angiogenic balance plays a causative role in endothelial cell injury. Increasing the knowledge about PE in twin gestation may improve patient's surveillance.